Fatores determinantes da intenção de denúncia ou do silêncio conivente da fraude contábil: um estudo à luz das teorias do comportamento planejado e do triângulo de fraude - Silva Filho, Gilberto Magalhães da (2019)
When faced with fraud, the accounting professional is in a dilemma about which decision to take: blowing the whistle, expected behavior, due to moral and ethical aspects; or remain silent, acting as an accomplice, for the risk of suffering negative reprisals of his behavior. Many elements can influence the choice, from personal aspects to incentives that start from the organization, in addition to the conflicts and uncertainties involved. In view of this, this thesis aimed to verify which factors can explain the reporting intention or the complicit silence of accounting fraud by accounting professionals. In order to give theoretical support to the work, we used the theory of planned behavior (TPB) of Ajzen (1991), and the fraud triangle theory (FTT) of Cressey (1953). The research model was expanded by incorporating other variables (ethical judgment, crime severity and position that the offender occupies) identified in the literature as influencers of the reporting behavior of accounting fraud. The sample consisted of 471 accounting professionals, and the methodology was divided into two parts, the first one for the construction and validation of the questionnaire, based on psychometric techniques, consisting of theoretical, empirical and analytical procedures. The theoretical procedures focused on the conceptual support that underlies the work and the operationalization of the construct in items. The empirical procedure defined the stages of application of the instrument, concluding with the evaluation of its quality. The analytical procedure defined the statistical processes used on the data that resulted in a valid instrument. The second part provided a detailed description of the analysis techniques used to answer the research object: correlation analysis, ordinal logistic regression and multiple regression. The research findings demonstrated that the factors belonging to TPB (attitudes, subjective norms and perceived behavioral control) can predict the behavioral intentions (complicit silence and reporting intention) of accounting professionals. Positive judgment toward denunciation (attitudes) and peer pressure (subjective norms) increase the probability of the professionals will report fraud, and the greater the barriers (perceived behavioral control) that may make denunciation more difficult, the greater the chances of them remain silent. The level of ethical judgment has proved to be a determinant of behavioral intentions, with positive effect, to at least one of the factors of the ethical dimension (social justice, relativism and contractualism). The existence of economic rewards is not relevant in the personal evaluation (attitudes) of fraud reporting. In conclusion, external reporting channels represent the primary route for professionals when considering the reporting of accounting irregularities. Therefore, it is the responsibility of the regulatory bodies (CVM, CFC etc.) to create communication channels so that professionals can report such fraud. The results are therefore relevant and contribute invaluable to the literature on reporting intention of accounting fraud in the national scenario, although further investigations are still needed. Reporting is an important component of accounting and internal controls, and it is the responsibility of government, entities and regulators to develop institutional policies to encourage it, as well as to ensure the protection of the potential reporter.